Characteristics and comprehensive evaluation of heavy metal concentrations in wild and cultivated morel mushrooms - Xiaolan Liu; Shaoxia Lin; Tingfei Deng; Anqin Gao; Fuxiao Wei; Tao Wei; Daoping Wang (International Journal of Food Properties, 2025)
To understand the degree of contamination, the concentrations of heavy metals, and the associated risks in different parts of wild and cultivated morel mushrooms from various origins, this study quantified seven heavy metals and conducted evaluations of safety, pollution levels, and health risks. The concentrations of Pb, Hg, Cu, and Zn were higher in wild morel mushrooms than in cultivated ones, while the concentrations of As, Hg, Cu, and Zn were higher in the caps than in the stalks. Overall, wild morel mushrooms exhibited a stronger capacity for bioaccumulating heavy metals, especially in the caps. The contents of As and Hg were both below the maximum limit values, indicating a safe level. However, Cu, Pb, and Cd in different samples, suggested varying degrees of contamination and these elements were identified as the main pollution contributors. The total non-carcinogenic risk (HI) value for children is higher than that for adults. Cd and Cu are the primary contributors to the total non-carcinogenic risk (HI) in both cultivated and wild morel mushrooms. The carcinogenic risk (CR) values of Cd, As, and Cr in all samples indicated potential carcinogenic risks. The carcinogenic risk for children is approximately twice that for adults. In summary, the heavy metal risk in morel mushrooms is higher in wild than in cultivated ones, higher in the caps than in the stalks, and higher for children than for adults. Therefore, it is necessary to strengthen environmental control and consumption guidance in production areas to reduce health risks.